Morphological evaluation of maxillary second molars with fused roots: a micro‐CT study. (10th March 2017) - Ordinola‐Zapata, R.; Martins, J. N. R.; Bramante, C. M.; Villas‐Boas, M. H.; Duarte, M. H.; Versiani, M. A.
Abstract: Aim: To evaluate the internal and external morphologies of fused‐rooted maxillary second molars by means of micro‐computed tomography (micro‐CT) analysis. Methodology: A total of 100 fused‐rooted maxillary second molars from a Brazilian subpopulation were divided into six groups according to the root morphology. The samples were scanned at a resolution of 19.6 μm and evaluated with regard to the external morphology of the roots, the root canal configuration, the percentage frequency of C‐shaped canals and isthmuses, as well as the morphology of the root canal system at 1, 2 and 3 mm from the anatomical apex of the fused roots. Results: The most prevalent root canal fusions were type 1, mesiobuccal root fused with distobuccal root (32%), followed by type 3, DB root fused with P root (27%), and type 4, MB root fused with DB root, and P root fused with MB or DB roots (21%). The prevalence of C‐shaped root canal systems were 22%. Depending on the type of root fusion, the percentage frequency of isthmuses in the apical level varied from 9.3% to 42.8%, whilst the presence of apical deltas ranged from 18.5% to 57.1% of teeth. Conclusions: The root canal system of maxillary second molars with fused roots may have a high incidence of merging canals, isthmuses, apical deltas and C‐shaped configurations.